Local Phase Transformation Strengthening at Microtwin Boundaries in Nickel-Based Superalloys. (1st October 2022) - Egan, A.J.; Xue, F.; Rao, Y.; Sparks, G.; Marquis, E.; Ghazisaeidi, M.; Tin, S.; Mills, M.J.
Abstract: This work investigated two similar polycrystalline alloys, differing by only 1 at% Nb content, which elucidated its effect on local phase transformation strengthening during high temperature creep. Compression creep tests were conducted at 750 °C and 600 MPa to 0.5% strain, resulting in deformation dominated by microtwinning. Higher Nb alloy RRHT5 exhibited superior creep strength to RRHT3 in terms of minimum creep rate. The deformation microstructures were characterized via atomic resolution scanning transmission electron microscopy and energy-dispersive spectroscopy, as well as atom probe tomography, which revealed a novel local phase transformation along microtwin interfaces in RRHT5. Orientation specific cECCI and analysis of superlattice intrinsic and extrinsic stacking faults in this alloy deconvolved strengthening effects of other local phase transformations. Density functional theory calculations complemented the experimental results and suggested this was χ phase formation. Increased creep strength of RRHT5 was attributed to local phase transformation along microtwin interfaces, which inhibited deleterious thickening of microtwins and rapid strain accumulation. Graphical abstract: Image, graphical abstract